Answer:
There are two types of exponential functions: exponential growth and exponential decay. In the function f (x) = bx when b > 1, the function represents exponential growth. In the function f (x) = bx when 0 < b < 1, the function represents exponential decay.
Step-by-step explanation:
Answer: (3x−2)(4x−1)
Step-by-step explanation:
<em>Start factoring with -11x.</em>
12x^(2)-11x+2
12x2+(−8−3)x+2
12x2+(−8x−3x)+2
12x2−8x−3x+2
<em>Factor the highest common denominator of each group.</em>
<em>Group the first two terms and the last two.</em>
(12x2−8x)+(−3x+2)
<em>Factor the highest common denominator (MCD) of each group.</em>
<em>4x(3x−2)−(3x−2)</em>
<em>Factoring the highest common denominator 3x−2.</em>
(3x−2)(4x−1)
Answer:
B. 3.
Step-by-step explanation:
OK lets try again.
The slope of the secant = slope of the tangent at a certain point ( The Mean Value Theorem).
Slope of the secant = f(5) - f(2) / (5 - 2)
= [(25-3) / (5-1) - (4-3) / (2-1)] / 3
= (22/4 - 1) / 3
= 9/2 / 3
= 9/6
= 3/2.
The derivative at c = the slope of the tangent at c.
Finding the derivative:
f'(x) = [2x(x - 1) - (x^2 - 3) ]/ (x - 1)^2 (where x = c).
= (x^2 - 2x + 3)/ (x - 1)^2 = the slope.
So equating the slopes:
(x^2 - 2x + 3) / (x - 1)^2 = 3/2
2x^2 - 4x + 6 = 3x^2 - 6x + 3
x^2 - 2x - 3 = 0
(x - 3)(x + 1) = 90
x = 3 , -1
x can't be -1 because we are working between the values 2 and 5 so
x = c = 3.
Answer:
6.245
Step-by-step explanation:
........... .....